PEMBELAJARAN INKUIRI TERBIMBING PADA SISWA KELAS V SDN BALONGGEMEK 1 JOMBANG - Yoggy Febriawan; Subanji Subanji; Syamsul Hadi (Graduate School of Universitas Negeri Malang, 2016)
This research was conducted with the aim to describe how the guided inquiry learning in mathematics for elementary school students in Class V. The descriptive qualitative research is used as the design of this study. The data collection procedures such as observasion, interviews and documentation is used. Analysis of the data used in this study is an interactive analysis. In the learning activities, there are using three components of the data analysis: data reduction, data presentation and verification. Based on the data analysis, it was concluded that the fifth grade teacher at SDN Balonggemek 1 Jombang has been applied the guided inquiry learning in Mathematics, even though the application of guided inquiry learning is not fulfill a proximately.Penelitian ini dilaksanakan dengan tujuan untuk mendeskripsikan bagaimana pembelajaran inkuiri terbimbing pada mata pelajaran matematika untuk siswa Sekolah Dasar Kelas V. Rancangan penelitian pada penelitian ini menggunakan rancangan penelitian kualitatif deskriptif. Peneliti menggunakan prosedur pengumpulan data berupa observasi, wawancara dan dokumentasi. Analisis data yang digunakan dalam penelitian ini yaitu analisis interaktif. Pembelajaran ini terdapat tiga komponen analisis data, yaitu reduksi data, penyajian data, dan verifikasi. Berdasarkan analisis data, didapatkan hasil bahwa guru kelas V di SDN Balonggemek 1 Jombang sudah menerapkan pembelajaran inkuiri terbimbing pada mata pelajaran matematika dengan cukup baik, walaupun dalam penerapan pembelajaran inkuiri terbimbing belum berjalan secara maksimal.